“It makes me angry. REALLY angry”: exploring emotional responses to climate change education - Whitehouse, Sarah; Jones, Verity (JSSE - Journal of Social Science Education, 2022)
Consideration of emotional response to climate education in a primary classroom Exploration of emotions that teaching about climate change may raise for teacher, researcher and pupil Identification of gender and cultural bias in children’s climate mitigation visions Use of three stage approach to climate education with emotion navigated, not ignored Purpose: Climate change education and the emotional consequences this topic raises in the classroom has been largely ignored by researchers. This paper considers the emotional response to climate education in a primary classroom (age 9-10 years) in England and begins to explore the emotions that teaching about climate change may raise for both teacher, researcher and pupil. Design: Part of a long- term ethnographic project in a school in England. Analysis of c60, 9-10-year olds drawings, participant observation notes and research diaries. Limitations: This is a small study - further research with larger numbers, different ages and in different geographical regions are required with both pupils and teachers. Practical implications: This work identifies pedagogies that allow injustices children identify to be explored with emotional responses being navigated rather than ignored. Such approaches support wellbeing in the face of growing numbers of young people suffering from eco-anxiety.